Life Style-Related Diseases of the Digestive System: Gene Expression in Nonalcoholic Steatohepatitis Patients and Treatment Strategies - Masato Yoneda; Hiroki Endo; Yuichi Nozaki; Ayako Tomimoto; Toshio Fujisawa; Koji Fujita; Kyoko Yoneda; Hirokazu Takahashi; Satoru Saito; Tomoyuki Iwasaki; Shogo Yamamoto; Shuichi Tsutsumi; et al. (Elsevier, 2007)
Nonalcoholic steatohepatitis (NASH) is a subset of nonalcoholic fatty liver disease (NAFLD) and sometimes progresses to cirrhosis and liver failure. We analyzed the expression profiles of approximately 50,000 genes and biological pathways in NASH patients in comparison with simple steatosis patients by using the analytical technique of GSEA (Gene Set Enrichment Analysis) by DNA microarrays. Although expressions of various genes were altered, GSEA showed clearly lower expression of nuclear receptors, including the peroxisome proliferator-activated receptor gamma (PPARγ) pathway. In a preliminary study we therefore investigated the therapeutic effect of low-dose pioglitazone (15 mg/day per body for 24 weeks), a synthetic ligand for PPARγ, in 12 NASH patients. A decrease in aminotransferase (ALT) values to within the normal range was observed in 7 (58.3%) of the patients, and because the dose of pioglitazone was lower than that ordinarily used, no side effects, such as fatigue, lower extremity edema, or weight gain, were observed. In conclusion, the results confirmed involvement of the PPARγ pathway in NASH and the therapeutic utility of a PPARγ ligand. Keywords:: life style-related disease, nonalcoholic steatohepatitis (NASH), nonalcoholic fatty liver disease (NAFLD), microarray, Gene Set Enrichment Analysis (GSEA), pioglitazone